1999
DOI: 10.1210/jcem.84.6.5757
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin A and Inhibin B Responses to Gonadotropin Withdrawal Depends on Stage of Follicle Development1

Abstract: Previous studies demonstrate that inhibin A and B are differentially secreted across the menstrual cycle. To test the hypothesis that the responses of inhibin A and inhibin B to partial gonadotropin withdrawal are influenced by the stage of follicular development, a maximally suppressive dose of the Nal-Glu GnRH antagonist (150 microg/kg) was administered to normal cycling women during the midfollicular (MFP; n = 8), late follicular (LFP; n = 6), and midluteal phase (MLP; n = 5) to assess ovarian responsivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…They act by interfering with the feedback loop responsible for the secretion of FSH from the pituitary. In humans, both inhibin A and B could be secreted by females [ 50 , 51 ], whereas in adult men, inhibin B is the primary form [52] . Our results revealed that in patients with LUAD, INHA expression was significantly higher in males than in females ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They act by interfering with the feedback loop responsible for the secretion of FSH from the pituitary. In humans, both inhibin A and B could be secreted by females [ 50 , 51 ], whereas in adult men, inhibin B is the primary form [52] . Our results revealed that in patients with LUAD, INHA expression was significantly higher in males than in females ( Fig.…”
Section: Discussionmentioning
confidence: 99%